Paradigma Penelitian - Sutarno Haryono (Institut Seni Indonesia Surakarta, 2010)
Research is an attempt to understand facts in a rational empirical way, using a certain procedure in accordance with the method chosen by the researcher. There are two kinds of research, namely quantitative and qualitative. In the research of a particular work, program, or event, using a holistic critical approach, its quality should be viewed from the perspective of its background, its objective formal conditions, and its impact.Â Keywords: Research, quantitative, qualitative, holistic critical.